CONCEPTUALIZING CREATIVE ECONOMY - Krawiec, Magdalena; Noga, Marian (Torun International Studies, 2018)
In the present papers, the authors analyse the new phenomenon in the global economy, which is creative economy. It is only since 1998, when the Ministry of Culture of Great Britain announced “the map” of creative industries in Great Britain, the world-wide professional economic literature has launched intensive studies over the entirety of creative economy, the foundation of which were cultural industries. Creative industries constitute a sharply delineated economic structure, referred to by the authors as a structural entity which yield itself to structural analysis. The aim of the paper is an attempt to define creative economy as a structural entity, which would entail certain consequences in an economic theory as well as in the practices of both domestic and global economy.